QUANTITATIVE ANALYSIS OF GYRA AND GYRB KNOWN MUTATIONS IN DRUG-RESISTANT MYCOBACTERIUM TUBERCULOSIS STRAINS TREATED WITH OFLOXACIN - RAMASAMY, PUSHPARAJU; SOUNDERRAJAN, VIGNESH; HARSHAVARDHAN, SHAKILA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of the study is to measure the minimum inhibitory concentrations (MICs) of ofloxacin antibiotic from gyrA and gyrB mutations present in fluoroquinolones (FQs) resistant strains of Mycobacterium tuberculosis (MTB) and to further concentrate the potential association between gene mutations and phenotypic resistance based on their MICs. Methods: Different levels of ofloxacin MICs levels were detected in 31 archived multi drug-resistant MTB isolates showing gyrA mutations in codon at A90V, S91P, D94A, D94N/Y, D94 G, and D94H and two gyrB probes (N538D and E540V). The MIC determinations were made using the 1% proportion method. Results: Genotypic assay detected 32 mutations in the gyrA (n=29) and gyrB (n=3) genes among the 31 FQs resistant isolates. Most frequently seen in gyrA mutations at codon D94G (n=16; 50%), these mutations had a clearly elevated MIC level from 2 to 16 μg/ml, that was phenotypically resistant. The A90V mutation region consistently exhibited the lowest levels of ofloxacin resistance, with three out of eight (37.50%) of these isolates had a MIC of <2 μg/ml. In addition, a further strain of S91P mutations for MIC was determined to be less than the critical concentration (CC). These low levels of resistance have been detected in a phenotypic manner which is noticeable in the study. Furthermore, fewer mutations in codons at D94A, D94N/Y were identified. Three wild-type absent isolates from gyrB QRDR were identified and the MIC of those strains for ofloxacin was lower than the critical cutoff value. Conclusion: Based on the results, it is shown that different resistance mutations were associated with different levels of MICs and the current concentration for MGIT will be lowered from 2 μg/ml to 1 μg/ml for the ofloxacin drug.